2011
DOI: 10.1590/s0103-50532011000400011
|View full text |Cite
|
Sign up to set email alerts
|

QSPR Modeling using Catalan Solvent and Solute Parameters

Abstract: A área de correlação quantitativa entre estrutura e propriedade (QSPR) pode beneficiar-se de descritores moleculares que representam interações intermoleculares. Catalan desenvolveu um método de escalas solvatocrômicas para solventes que pode ser explorado para esta finalidade. Neste trabalho, escalas de solvente de Catalan foram usadas como descritores moleculares para o desenvolvimento de modelos QSPR, e para o cálculo de novos descritores de soluto para uso posterior em QSPR. As escalas Catalan para o solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…From a mathematical viewpoint, it is possible to compute J i terms at one temperature, and employ these constants for solubility prediction of pharmaceutical compounds in the binary mixtures at other temperatures by using the solubility data in the mono-solvents as input values as has been shown in earlier works [14,15,[21][22][23][24][25][26]. This numerical method provided acceptable and accurate predictions however two data points are required at each temperature of interest.…”
Section: Methodsmentioning
confidence: 99%
“…From a mathematical viewpoint, it is possible to compute J i terms at one temperature, and employ these constants for solubility prediction of pharmaceutical compounds in the binary mixtures at other temperatures by using the solubility data in the mono-solvents as input values as has been shown in earlier works [14,15,[21][22][23][24][25][26]. This numerical method provided acceptable and accurate predictions however two data points are required at each temperature of interest.…”
Section: Methodsmentioning
confidence: 99%
“…The solubility of flavonoids and phenolic compounds is heavily influenced by their physicochemical nature, the degree of polymerization, and interaction with other constituents in the plant matrix, as well as by the formation of insoluble complexes. 22,23 This makes the extraction of these compounds very challenging, since there is no uniform approach to the extraction of all flavonoids or of any specific subclass of phenolic compounds whatsoever. 24 The characterization of phenolic compounds present in stinging nettle leaf extract showed that it is rich in flavonol glycosides, and it is known that glycosylation increases the polarity of flavonoids.…”
Section: T a B L Ementioning
confidence: 99%
“…In solubility correlation almost all kinds of descriptors have been used. Around half of the models use logP as one of descriptors in modelling (Dearden, 2006 (Dearden, 2006;Katritzky et al, 2010;Jouyban et al, 2010b). Other descriptors have been used as well, and a number of mixtures of the mentioned parameters are used, too.…”
Section: Toxicity and Drug Testing 198mentioning
confidence: 99%